The Body Without Organs in the 21st Century Spanish Poetry: Theory and Symbol - Fernández Martínez, Sergio (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
Through the concept "body without organs", Antonin Artaud questions the organic order of reality, considered by him pernicious for the subject and for existence itself. Gilles Deleuze takes up the notion to develop his theory of the event and of the difference, and through it he generates an analytical definition of desire. This paper analyses the dialogue between this concept and the 21st century Spanish poetry through three poetry books: Cuerpo sin mí [Body Without Me], by Eduardo Moga, La piel o el cuerpo [The Skin or the Body], by Leticia Fernández-Fontecha, and Phantasmagoria [Phantasmagoria], by Sara Torres. Expression of the power of affect in real experience, the body without organs appears as the constitutive axis of these texts in the purest Deleuzian sense, allowing us to rethink the limits and scope of contemporary Spanish lyric.
Keywords: Body Without Organs; Gilles Deleuze; Body Studies; Poetry